Power Outages and Technical Efficiency of Manufacturing Firms: Evidence from Selected South Asian Countries - Luqman, Muhammad; Haq, Mirajul; Ahmad, Iftikhar (International Journal of Energy Economics and Policy, 2021)
The deficiency of secure and reliable electrical power is a constraint to firm performance and its competitiveness in developing countries. Several countries in the south Asian region face electricity shortages leading to frequent power outages. This study investigate the effect of power outages on the technical efficiency of firms in selected South Asian countries. The study employed the stochastic frontier approach to estimate the technical efficiency of firms. We use the OLS and Beta regression to estimate the effect of power outages on technical efficiency of manufacturing firms. The results of the study reveal that power outages reduce the technical efficiency of manufacturing firms operating in selected South Asian countries. These results are robust to the alternative empirical specifications and estimation techniques. Overall results suggest that South Asian countries should invest in the secure and reliable energy to amplify productivity growth and resulted competitiveness of firms in global market. Keywords: Technical Efficiency, Power Outages, Manufacturing Firms, South Asia JEL Classifications: D21, D22, O12 DOI: https://doi.org/10.32479/ijeep.10584